Increasing the confidence of students at the Nurul Mukhlasin Islamic Boarding School through participatory discussion methods - Liddya Ganda Asmara; Linda Setiawati; Dimas Saputra (Jurnal Abmas, 2025)
Self-confidence is a crucial aspect of personal development, particularly for students in Islamic boarding schools who face numerous social and academic challenges. Self-confidence development activities at Nurul Mukhlasin Islamic Boarding School involve community service initiatives designed to enhance students' self-confidence and self-esteem. This service is provided due to the low level of self-confidence that hinders students' active participation in various activities within and outside the Islamic boarding school. The methods employed are lectures and participatory discussions, which involve direct interaction between facilitators and students to develop communication and self-expression skills. Twenty-two students participated in the activity. We evaluated by measuring changes in self-confidence levels before and after the activity through the distribution of questionnaires and direct observation. The evaluation results showed a significant increase in aspects of self-confidence, public speaking skills, involvement in discussions, and self-expression before and after the activity, which had a positive impact on students' communication skills, social interactions, and learning motivation. These findings confirm the benefits and effectiveness of the participatory discussion method as a medium for self-development in Islamic boarding schools and are recommended for continuous implementation in student development programs.   Abstrak Kepercayaan diri merupakan aspek penting dalam perkembangan pribadi, terutama bagi santri di lingkungan pondok pesantren yang menghadapi tantangan sosial dan akademik beragam. Kegiatan pembinaan kepercayaan diri di Pondok Pesantren Nurul Mukhlasin merupakan pengabdian masyarakat yang bertujuan meningkatkan kepercayaan diri santri. Pengabdian ini dilaksanakan karena rendahnya tingkat kepercayaan diri yang menghambat partisipasi aktif santri dalam berbagai kegiatan di dalam maupun di luar pesantren. Metode yang digunakan adalah ceramah dan diskusi partisipatif yang melibatkan interaksi langsung antara fasilitator dan santri untuk membangun kemampuan komunikasi dan ekspresi diri dengan jumlah partisipan kegiatan sebanyak 22 orang santri. Evaluasi dilakukan dengan mengukur perubahan tingkat kepercayaan diri sebelum dan sesudah kegiatan melalui penyebaran kuesioner dan observasi langsung. Hasil evaluasi menunjukkan peningkatan signifikan pada aspek kepercayaan diri, kemampuan berbicara di depan umum, keterlibatan dalam diskusi, serta ekspresi diri sebelum dan sesudah kegiatan yang berdampak positif pada kemampuan komunikasi, interaksi sosial, dan motivasi belajar santri. Temuan ini menegaskan manfaat dan efektivitas metode diskusi partisipatif sebagai media pengembangan diri di pondok pesantren dan direkomendasikan untuk diterapkan secara berkelanjutan dalam program pembinaan santri. Kata Kunci: kepercayaan diri, motivasi belajar, pondok pesantren